Referral criteria: perceptions and experiences of district nursing students in Northern Ireland. (2nd November 2021) - Young, Charlene; Reid, Bernie
Abstract : An ever-ageing population and widening health inequalities intensify the complexity of care that is now delivered within community settings by district nurses. Appropriate referral criteria are required to facilitate the enhancement of efficient and equitable district nursing service provision. This study aimed to explore district nursing students' perceptions and experiences of district nursing referral criteria in Northern Ireland. A qualitative phenomenological approach was adopted using a purposive convenience sample of 10 district nursing students. Data were collected during online focus group interviews and analysed using a thematic framework. Four themes emerged: referral criteria; insight and inconsistency; task versus patient-centred care; and misunderstanding the service and referral quality. The themes reflect a lack of consensus with respect to referral criteria, contributing to inappropriate and poor-quality referrals. Appropriate and quality referrals to district nursing services are key to assuring sustainable service provision. Suitable access to district nursing services may be enhanced by developing consensus referral criteria.